GAS CHROMATOGRAPHY MASS SPECTROMETRY (GC-MS) ANALYSIS AND DOCKING STUDIES OF ANDROGRAPHIS PANICULATA AGAINST DENGUE FEVER - Somarathinam, Kanagasabai; Kothandan, Gugan; Devadasan, Velmurugan (Innovare Journal of Life Sciences, 2018)
Objective: To evaluate gas chromatography- mass spectrometry (GC-MS) analysis and molecular docking studies of ethanol extract of Andrographis paniculata (Burm.f.) against type 2 dengue virus (DEN2). Methods: The ethanol extract of A. paniculata compounds were identified by GC-MS analysis. These compounds were further analysed for their activities against NS2B/NS3 protease of DEN2 by molecular docking studies. Results: The nine compounds obtained from the ethanol extract of A. paniculata were characterized and docked. Among these nine compounds, Vor-diazepam,3-[[N-hydroxymethyl]aminocarbonyloxy], Dasycarpidan-1-methanol, acetate (ester), Ethanol, 2-(9, 12-octadecadienyloxy)-, (Z, Z), Gibb-2-ene-1,10-dicarboxylicacid4a,7-dihydroxy-1-methylene-1,4a-lactone,10 methylester, (1a,4aa,4ba,10a) were found to show better interaction energetically and also showed crucial interactions with the active site of NS2B/NS3 protease. Thus A. paniculata is suggested to be a medicinally important plant to cure dengue fever. Conclusions: From the result, it can be concluded that the crude extract of A. paniculata compounds positively inhibit the activities of NS2B/NSB protease of DEN2 thus by preventing the dengue viral infection. This strategy reflects a logical progression for an early stage drug discovery which can be used to identify new drug candidates.Â